THE ESSENCE OF POLYGAMY AND ITS ASSOCIATION WITH INDONESIAN MARRIAGE LAW - Muh. Zaitun Ardi; Mujiburrahman (Al-Risalah, 2022)
This study aims to explain the substance of the possibility of polygamy and its relevance to Indonesian marriage law. Polygamy has existed in the pre -Islamic era until today. Islam does not forbid and advocate polygamy, but Islam came to regulate and limit the rules of Polygamy. The substance of polygamy can be seen from the context or nash of polygamy as well as Arab history in the Jahiliyyah period. Contextually Nash, Polygamy is allowed for widows and orphans with a limit of four wives and conditions of fairness. This verse was revealed because many Muslims died during the battle of Uhud which affected the high number of widows and orphans left to die with worrying conditions in terms of economic, social and educational. women are the property of their own wealth. So with this response, women are likened to animals and goods that can be traded regardless of a woman's rights. Basic Law of Polygamy in Islam Qur’an which puts forward the principles of justice and welfare in emergencies. The relevance of the provisions on polygamy in Marriage and the Compilation of Islamic Law is not fully in line with the substance or nash of the ability of polygamy in Islam but has led to the basis of Qur’an with the principle of justice, creating benefits and prevent damage. The reason for the possibility of polygamy is that there are more women than men and if monogamy continues to be maintained then there will be many practices of prostitution. This study uses a qualitative approach with the type of library research, which is a series related to the methods of collecting library data, reading, taking notes and processing research materials. The approach of seeking information from the problem that is being tried to find the answer. So, the theory of approach used is the legal approach, the normative approach and the descriptive approach. The subject of this thesis research is a descriptive approach, which describes polygamy in the Marriage Law in Indonesia from the perspective of Islamic jurisprudence. Furthermore, it examines the relevance of the provisions of polygamy in the Marriage and the Compilation of Islamic Law because it is not fully in line with the substance or text of the permissibility of polygamy in Islam.